ALK+ large B‐cell lymphoma: A rare variant of aggressive large B‐cell lymphoma mimicking carcinoma on cytology specimens. Issue 5 (20th February 2012) - Lin, Oscar; Koreishi, Aashiyana; Brandt, Suzanne M.; Arcila, Maria; Teruya‐Feldstein, Julie
Abstract Anaplastic lymphoma kinase positive large B‐cell LYMPHOMA (ALK+ LBCL) was recognized as a distinct entity by the 2008 WHO classification of lymphomas. Histologically, the tumor cells exhibit either plasmablastic or immunoblastic morphology, with characteristic granular staining for ALK. The purpose of this study is to evaluate the cytologic findings of ALK+ LBCL. The cytologic material obtained by needle biopsy from three cases of ALK+ LBCL was evaluated. All lesions were nodal and the cytologic material analyzed included air‐dried and alcohol‐fixed slides stained with modified Giemsa and/or HE stains. The following morphologic criteria were assessed: cellularity, cluster characteristics, cell size, cytoplasmic and nuclear characteristics, and background composition. The cytology specimens obtained from the needle biopsies were moderately to highly cellular and composed of a population of large cells with immunoblastic or plasmablastic morphology. Single cells were present in all three cases, but two cases also showed the presence of clusters with acinar and papillary architecture. Multinucleation was noted in all three cases. Amorphous metachromatic background material was noted focally in the modified Giemsa stained slides in all three cases. Immunostains performed on cytology specimens showed cytoplasmic immunoreactivity for ALK, with characteristic granular features. ALK+ LBCL is a rare recently recognized type of lymphoma with unique morphologic and immunophenotypic findings that can mimic epithelial tumors. Recognition of this potential diagnostic pitfall is critical to prevent unnecessary additional work‐up and mistreatment. Diagn. Cytopathol. 2013. © 2012 Wiley Periodicals, Inc.